(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aimed to identify the relationship between marital compatibility and coping strategies among working women in the Negev region. The study used the correlational descriptive approach. To achieve the goals of the study, the researcher used two measures: one for marital compatibility and another one for coping strategies. After verifying their validity and reliability, they were applied to a sample of (452) women working in the Negev Region. The results showed that the degree of total marital compatibility among working women in the Negev Region was great, and the study found that there is a positive direct relationship between marital compatibility and its fields on the one hand and the dimensions of adaptation strategies on the other hand.. The results showed that there were no statistically significant differences in the degrees of marital compatibility among working women in the Negev Region according to the variablesof monthly income, number of children, and place of residence, while statistically significant differences appeared in the degrees of marital compatibility among working women in the Negev Region according to the age variable in favor of the working women aged (18-23). The results also showed statistically significant differences in the degrees of coping strategies for working women in the Negev region according to the monthly income variable in favor of working women whose monthly income is moderate and high, and for the age variable in favor of working women agedmore than 30 years In addition, the results showed that there were no statistically significant differences in the degrees of coping strategies for working women in the Negev Region according to the variables of the number of children and the place of residence.